Experimental Investigation and Statistical Modeling of FRP Confined RuC Using Response Surface Methodology - Feng, Xiong; Tufail, Rana Faisal; Zahid, Muhammad (Civil Engineering Journal, 2019)
Scrap tires that are dumped to landfill is a serious problem in China and rest of the world. The use of rubber in concrete is an effective environmental approach to reduce the amount of scrap tires around the world. However, the loss in compressive strength of concrete is a major drawback of rubberized concrete. In this paper, the fiber reinforced polymer (FRP) confinement technique is used to overcome the drawbacks of rubberized concrete (RuC). A total of sixty six RuC cylinders were tested in axial compression. The cylinders were cast using recycled rubber to replace, a) 0-50 percent fine aggregate volume, b) 0-50 percent coarse aggregate volume, and c) 40-50 percent fine and coarse aggregate volume. Twenty seven cylinders of the latter mix were then confined with one, two and three layers of CFRP jackets. Concrete suffered a substantial reduction in compressive strength up to 80 percent by fine and coarse aggregate replacement with rubber content. However, CFRP jackets recovered and further enhanced the axial compressive strength of RuC up to 600% over unconfined RuC. SEM was performed to investigate the microstructural properties of RuC. Statistical models were developed on the basis of experimental tests for FRP confined RuC cylinders using response surface method. The effect of variable factors; unconfined concrete strength, rubber replacement type and number of FRP layers on confined compressive concrete strength was investigated. The regression analysis was performed to develop the response equations based on quadratic models. The predicted and experimental test results were found in good agreement as the variation between experimental and predicted values were less than 5%. Furthermore, the difference between predicted and adjusted R2 was found to be less than 0.2 which shows the significance of the statistical models. These proposed statistical models can provide a better understanding to design the experiments and the parameters affecting FRP-confined RuC cylinders.